Technology Readiness and Acceptance Model in the Evaluation of the Singmanfaat System at the West Java Provincial Forestry Service - Manaf, Khaerul; Hawari, Muhammad; Gunawan, Yanyan; Jamaludin, M. Rifqi Azkiya (JESII: Journal of Elektronik Sistem InformasI, 2025)
Using the Technology Readiness and Acceptance Model (TRAM) approach, the research investigates the readiness and acceptance of the SINGMANFAAT application among users working for the West Java Provincial Forestry Service. Optimism and insecurity were discovered to have a substantial influence regarding perceived utility and simplicity of use, according to the findings of the research that involved 88 employees. The only thing that was affected by innovativeness was the convenience of use; pain was not altered. According to the findings of the survey, enhancing user comfort and bolstering faith in data security are two of the most important factors in ensuring successful adoption of technology. The findings can serve as a reference for the implementation of information systems that are based on technology in government entities.